Respiratory Support for Patients with Chronic Respiratory Failure: the Necessity of a Long-Term Homecare Ventilation Program - Abai Baigenzhin; Alexey Pak; Lina Zaripova; Zhanar Zarkumova; Elmira Chuvakova (National Scientific Medical Center, 2024)
Severe respiratory failure, resulting from a wide range of acute and chronic diseases such as chronic obstructive pulmonary diseases, obstructive sleep apnoea, obesity hypoventilation syndrome (Pickwickian syndrome), COVID-19, bilateral pneumonitis, kyphoscoliosis, acute respiratory distress syndrome, amyotrophic lateral sclerosis, Guillain-Barré syndrome, and others, poses a significant challenge for healthcare systems worldwide. Treating severe respiratory failure often requires long-term or lifelong respiratory support, which places a heavy burden on both patients and healthcare systems. Despite the availability of free comprehensive care for patients with chronic kidney failure and heart failure, those requiring long-term respiratory support are often deprived of adequate medical and social assistance. This gap in care leads to frequent hospitalizations, disability, and premature death of patients with severe respiratory failure, further straining healthcare resources and increasing social tension. The solution of the problem is an organisation of ambulatory centre for homecare respiratory support for patients with severe chronic respiratory failure. Homecare respiratory support demonstrated worldwide cost-effectiveness by significantly enhancing patients clinical and social outcomes, restoring their work capacity, and reducing the need for hospitalizations. This article emphasizes the necessity of a comprehensive homecare respiratory support system and highlights how inadequate assistance can result in frequent hospitalizations, increased disability, and premature death, thereby imposing an additional strain on the healthcare system.